1999
DOI: 10.1128/aem.65.7.2877-2894.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Analysis Techniques: What Do Cell Preparation Protocols Do to Cell Surface Properties?

Abstract: Cell surface analysis often requires manipulation of cells prior to examination. The most commonly employed procedures are centrifugation at different speeds, changes of media during washing or final resuspension, desiccation (either air drying for contact angle measurements or freeze-drying for sensitive spectroscopic analysis, such as X-ray photoelectron spectroscopy), and contact with hydrocarbon (hydrophobicity assays). The effects of these procedures on electrophoretic mobility, adhesion to solid substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(106 citation statements)
references
References 53 publications
(60 reference statements)
5
96
1
4
Order By: Relevance
“…Bacterial cells were centrifuged for 15 min at 190g and resuspended in the desired media for the force measurements (described below). This low centrifugal force was chosen because previous results from our laboratory have shown that it is sufficient to pellet E. coli, but does so without causing any artifacts in cell surface characteristics and adhesion behavior (Bell and Camesano, 2005), as can be found when high forces are applied to bacteria (Pembrey et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial cells were centrifuged for 15 min at 190g and resuspended in the desired media for the force measurements (described below). This low centrifugal force was chosen because previous results from our laboratory have shown that it is sufficient to pellet E. coli, but does so without causing any artifacts in cell surface characteristics and adhesion behavior (Bell and Camesano, 2005), as can be found when high forces are applied to bacteria (Pembrey et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Hydrophobicity was determined with the microbial adhesion to hydrocarbons method (Pembrey et al, 1999;Walker et al, 2005), where percentage partitioning of cells into dodecane was measured as cell hydrophobicity. To do this, 4 ml of bacteria suspension of known optical density (OD) and 1 ml of dodecane were vigorously mixed in a test tube for 2 min and left to stand for 15 min to allow phase separation.…”
Section: Bacteria Growth and Cell Characterizationmentioning
confidence: 99%
“…Th e zeta-potential measurements are in agreement with previous studies in which it was demonstrated that centrifugation can alter the surface charge of bacteria. For example, Pembrey et al (1999) reported that harvesting by high-speed centrifugation (15,000 × g) generally reduced the net surface charge of E. coli. Th is eff ect was attributed to removal of materials from the cell surface and thus generating a new and very diff erent microenvironment interface.…”
Section: Electrophoretic Mobilitymentioning
confidence: 99%